Razor wire women : prisoners, activists, scholars, and artists - Lawston, Jodie Michelle, 1977-; Lucas, Ashley E., 1979- (SUNY series in women, crime, and criminology., 2011)
Offering nuanced portraits of women's lives inside razor wire and prison walls, Razor Wire Women puts incarcerated women in dialogue with scholars, artists, educators, and activists who live outside of prisons but work on issues connected to the prison industrial complex. Women make up the fastest-growing group within the U.S. prison population, yet prison scholarship largely overlooks the struggles of incarcerated women, and their voices are often silenced both in and out of the prison infrastructure. From the vantage points of those both inside and outside of prisons, this collection of essays and art illuminates many of the distinct experiences and concerns of incarcerated women, including abuse and rape; the policing of women; incarcerated motherhood; mental health issues in prisons; incarcerated women's artistic and cultural production; and prisons' impact on families, health, and sexuality. Combining the transcendence, hope, and clarity of art with powerful analytical and conceptual tools, Razor Wire Women reveals the gendered dimensions of incarceration in the United States.